Pengaruh Kepuasan Kompensasi Dan Lingkungan Kerja Terhadap Motivasi Serta Dampaknya Pada Kepuasan Kerja Karyawan Perusahaan Daerah Air Minum (Pdam) Kabupaten Bantul Daerah Istimewa Yogyakarta - Citra Arta, Deddy Novie; Harsono, Harsono (208-7721)
Employees are an important asset of the company. The company will not be able to conduct their business activities, without the support of employees. This study aimed to examine the effect of compensation satisfaction toÂ  motivation, the effect of job environment to motivation, the effect of compensation satisfaction to job satisfaction, the effect of job environment to job satisfaction and the effect of motivation to employee job satisfaction. samples in the study of 120 people, which is taking all employees who work at Perusahaan Daerah Air Minum (PDAM) in the district of Bantul. This research method is quantitative analysis and technical of analysis the data using structural equation modeling to test the validity, reliability test, normality test, outliers, goodness of fit models test and regression test. The results of this study, namely compensation satisfaction has a positive influence directly and significantly to the motivation of 0,495, a job environment has a positive influence directly and significantly to motivation of 0,343, compensation satisfaction has a positive and significant influence directly to job satisfaction of 0,270 or indirectly through motivation of 0,265, the job environment has a positive and significant influence directly to job satisfaction of 0,288 or indirectly through motivation of 0,184 and motivation has a positive and significant influence to job satisfaction of 0,535. Based on the results of this study, the management of local water companies need to increase the level of compensation of employees, so the employees basic needs fulfilled and will increase employee motivation and job satisfaction of employees has increased. However, the work environment also need to be considered, in order to create a comfortable working atmosphere and harmony within the company.